Miss Kraft is daft! - Gutman, Dan.; Paillot, Jim (New York : Scholastic, 2013)
When Mr. Granite goes home sick, the wackiest substitute teacher in the history of the world comes to A.J.'s class and teaches math lessons using magic tricks.
2-5.
7-10.
3.5.
Accelerated Reader AR
5990
Keywords: Substitute teachers -- Juvenile fiction; Magic tricks -- Juvenile fiction; Human behavior -- Juvenile fiction; Schools -- Juvenile fiction; Humorous fiction